Innovation in care for individuals with cognitive impairment: Can reimbursement policy spread best practices?. Issue 10 (16th September 2017) - Borson, Soo; Chodosh, Joshua; Cordell, Cyndy; Kallmyer, Beth; Boustani, Malaz; Chodos, Anna; Dave, Jatin K.; Gwyther, Lisa; Reed, Susan; Reuben, David B.; Stabile, Stephen; Willis‐Parker, Monica; et al.
Abstract: There is now an unprecedented opportunity to improve the care of the over 5 million people who are living with Alzheimer's disease and related dementias and many more with cognitive impairment due to brain injury, systemic diseases, and other causes. The introduction of a new Medicare care planning benefit—long sought openly by advocacy organizations and clinicians and badly needed by patients and families—could greatly improve health care quality, but only if widely and fully implemented. We describe the components of this new benefit and its promise of better clinical care, as well as its potential to create a new platform for clinical and health outcomes research. We highlight external factors—and some that are internal to the benefit structure itself—that challenge the full realization of its value, and we call for broad public and professional engagement to ensure that it will not fail.